Muggl: The Muenster generator of glass-box test cases - Tim A. Majchrzak; Herbert Kuchen (Westfälische Wilhelms-Universität Münster, European Research Center for Information Systems (ERCIS), 2011)
Testing is a task that requires much effort, yet it is essential for developing software. Automated test case generation (TCG) promises to relieve humans of manual work. We introduce Muggl (the Muenster generator of glass-box test cases), which is developed at our institute. Muggl generates test cases for Java bytecode. It symbolically executes code and uses constraint solving techniques. While papers on Muggl have already been published, no comprehensive introduction of the tool exist. This working paper fills this gap.
Keywords: 650; Software test; testing; test case generation; TCG; test automation; test tool